2022
DOI: 10.3390/d14121094
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variation of Strychnos spinosa Lam. Morphotypes: A Case Study at Bonamanzi Game Reserve, KwaZulu-Natal, South Africa

Abstract: Strychnos spinosa Lam. of the Loganiaceae family is associated with versatility, poverty eradication, and rural economic development. However, the morphological diversity of S. spinosa is not well documented. This limits efforts toward its improvement and commercial exploitation. This study aimed to characterize the variability, vegetative and reproductive traits, and heritability of S. spinosa morphotypes at Bonamanzi Game Reserve. The majority of the morphotypes had green, rough, round immature fruits with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…The grouping of morphotypes in the dendrogram according to the variation of pericarp texture, using SSR markers (Figure 4) confirms the similar grouping based on the morphological traits [3]. The exceptions where the morphotypes were previously grouped on their own using the morphological traits [3] but are associated with the others in the SSR analysis (Figure 4), would indicate that those morphotypes were expressing different phenotypic traits that were from the same genomic origin. This probably explains the fading of roughness in the pericarp texture for some morphotypes during fruit growth, which requires further investigation.…”
Section: Principal Coordinate Analysis and Phylogenetic Relationshipsupporting
confidence: 64%
See 4 more Smart Citations
“…The grouping of morphotypes in the dendrogram according to the variation of pericarp texture, using SSR markers (Figure 4) confirms the similar grouping based on the morphological traits [3]. The exceptions where the morphotypes were previously grouped on their own using the morphological traits [3] but are associated with the others in the SSR analysis (Figure 4), would indicate that those morphotypes were expressing different phenotypic traits that were from the same genomic origin. This probably explains the fading of roughness in the pericarp texture for some morphotypes during fruit growth, which requires further investigation.…”
Section: Principal Coordinate Analysis and Phylogenetic Relationshipsupporting
confidence: 64%
“…The population structure for K = 3 (Figure 2) and the highest delta value that occurred at K = 3 (Figure 1) indicated that the morphotypes can be divided into three subpopulations with admixed morphotypes amongst the subpopulations. This demonstrates a complex history of gene flow and admixtures among the different populations [38], which may have contributed to the observed morphological diversity of Strychnos spinosa [3]. The affinities produced by population structure (Figure 2) generally agreed with the genetic distance (Supplementary Materials) of closely related morphotypes GSR-GRO and GRP-GEO in sub-population K3.2, and closely related morphotypes GRR-GEF and GvRR-dGEO in subpopulation K3.3.…”
Section: Population Structuresupporting
confidence: 53%
See 3 more Smart Citations